Extrachromosomal sequences of hepatitis B virus DNA in peripheral blood mononuclear cells of acquired immune deficiency syndrome patients. - Noonan, C A (1986)
The primary etiologic agent of the acquired immune deficiency syndrome (AIDS) is a human T-lymphotropic retrovirus (the AIDS virus). However, the pathogenesis of this virus suggests that other cofactors may contribute to the development of clinically overt disease. The hepatitis B virus (HBV) has been implicated as a potential cofactor because HBV and AIDS virus infections frequently coexist, striking similarities exist in their epidemiologic patterns, and recent data indicate that HBV is lymphotropic. To establish the prevalence of HBV infections in lymphoid cells from individuals with AIDS-related disorders, sera and peripheral blood mononuclear cells (PBMC) from 16 males with AIDS virus infections were examined for the presence of HBV DNA by DNA X DNA blot hybridization. Fifteen (94%) of these individuals had serologic evidence of a recent or prior HBV infection. HBV DNA was detected in the PBMC of all of these patients, regardless of existing HBV serology. Among the 36 control individuals without AIDS-related symptomatology, PBMC-associated HBV DNA was detected in 8 of 14 carriers of hepatitis B surface antigen (HBsAg) and in 3 of 10 individuals immune to HBV, but it was absent from the PBMC of 12 individuals without HBV infection. In all instances, the HBV DNA was extrachromosomal and existed as replicative intermediates or high molecular weight oligomers of the viral genome. Replicative intermediates and serum-associated HBV DNA were detected in all hepatitis B e antigen-positive carriers, regardless of their clinical status. In contrast, the high molecular weight oligomers of HBV DNA were detected in the PBMC of all of the AIDS virus-infected patients examined, but in only 33% of those in the control group who had evidence of HBV infection. This finding suggests that a unique and complex HBV-host-cell interaction exists in patients infected with the AIDS virus.